2009
DOI: 10.1088/0004-637x/695/1/574
|View full text |Cite
|
Sign up to set email alerts
|

Electron Acceleration at a Low Mach Number Perpendicular Collisionless Shock

Abstract: A full particle simulation study is carried out on the electron acceleration at a collisionless, relatively low Alfven Mach number (M A = 5), perpendicular shock. Recent self-consistent hybrid shock simulations have demonstrated that the shock front of perpendicular shocks has a dynamic rippled character along the shock surface of low-Mach-number perpendicular shocks. In this paper, the effect of the rippling of perpendicular shocks on the electron acceleration is examined by means of large-scale (ion-scale) t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 42 publications
1
52
0
Order By: Relevance
“…The dependence of this mechanism on different shock parameters needs to be clarified, and in fact, in this work we find that this mechanism is not very efficient at realistic mass ratios. Also, using twodimensional PIC simulations Umeda et al (2009) showed that, for M A = 5 shocks, pre-acceleration in Buneman waves can be complemented by further energization due to scattering at the shock ripples, supporting the picture laid out by Burgess (2006). The energy spectrum of the electrons in this case, however, does not correspond to a power law tail, but is rather described by two Maxwellian distributions at different temperatures.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…The dependence of this mechanism on different shock parameters needs to be clarified, and in fact, in this work we find that this mechanism is not very efficient at realistic mass ratios. Also, using twodimensional PIC simulations Umeda et al (2009) showed that, for M A = 5 shocks, pre-acceleration in Buneman waves can be complemented by further energization due to scattering at the shock ripples, supporting the picture laid out by Burgess (2006). The energy spectrum of the electrons in this case, however, does not correspond to a power law tail, but is rather described by two Maxwellian distributions at different temperatures.…”
Section: Introductionsupporting
confidence: 65%
“…PIC simulations have been used by several authors to study the electron acceleration problem in nonrelativistic shocks (e.g., Amano & Hoshino 2007; Umeda et al 2009). For instance, using two-dimensional PIC simulations, Amano & Hoshino (2009) showed that efficient electron acceleration (with spectral index α = 2-2.5) can happen in a perpendicular, M A = 14 shock due to "shock surfing" of electrons on electrostatic waves from Buneman instability excited at the leading edge of the shock foot.…”
Section: Introductionmentioning
confidence: 99%
“…These regions then provide stronger Buneman instability which should lead to more efficient localized electron heating and acceleration (see Umeda et al 2009 for similar effects in low-Mach-number shocks). Due to the poorly resolved foot structure at the reverse shock, a detailed analysis of this possible connection between shock ripples and electron energization must be deferred to future work.…”
Section: Structure Of the Reverse Shockmentioning
confidence: 99%
“…For panel (b), we compensated the average velocity of all ions (see Figure 10), whereas for panel (c) on the right we compensated only the average motion of incoming ions. Umeda et al 2009Umeda et al , 2010Umeda et al , 2014. The ion temperature anisotropy arising from ion reflection at the shock can drive the Alfvén ion cyclotron (AIC) or the mirror instability in the shock ramp, and the resulting unstable modes have wavelengths of a few ion skin depths and propagate along the regular magnetic field, significantly contributing to ion isotropization and thermalization at the shock and downstream.…”
Section: Structure Of the Reverse Shockmentioning
confidence: 99%
“…A detailed initial setup for 2-D simulations of (quasi-)perpendicular shocks was described in our previous studies (Umeda et al, 2008(Umeda et al, , 2009(Umeda et al, , 2010(Umeda et al, , 2011(Umeda et al, , 2012a(Umeda et al, , b, 2014 and is not repeated here.…”
Section: Simulation Setupmentioning
confidence: 99%